Principle of Beneficial Owner in Corporate Crime - Muhammad Saleh; Abdul Jabar Rahim; arifai (Faculty of Law, Universitas Pekalongan, 2025)
This study aims to analyze the application of the principle of beneficial owners in corporate crimes in Indonesia. The background of this research focuses on the challenges of identifying beneficial owners within corporate structures that are often used to commit crimes, including money laundering and corruption. The method used is normative legal research with a juridical approach, where data is collected from laws and regulations and case studies. The results show that although the principle of beneficial owners has been regulated in positive law, its implementation is still not effective. This is due to a lack of understanding and compliance from corporations as well as weaknesses in supervision by the relevant authorities. This study recommends the need for reforms in regulations and increased supervisory capacity to ensure that beneficial owners can be identified and held legally accountable in cases of corporate crimes.